Transformasi Pedagogi Guru PAI dalam Perspektif TPACK di Era Digital: Kajian Sistematis terhadap Tren dan Model Pembelajaran - Hilyatul Auliya; Muhammad Fahmi (Studia Religia : Jurnal Pemikiran dan Pendidikan Islam, 2026)
The rapid development of digital technology has significantly transformed the landscape of education, including Islamic Religious Education (PAI), requiring teachers to integrate technology meaningfully into pedagogical practices. This study aims to analyze the transformation of PAI pedagogy through the Technological Pedagogical Content Knowledge (TPACK) framework in the digital era. Employing a Systematic Literature Review (SLR) approach, this research synthesizes findings from selected national and international scholarly articles to identify trends, integration models, as well as challenges and implications of TPACK implementation in PAI learning. The results reveal that although there has been a shift from conventional to technology-integrated pedagogy, most practices remain at an adaptive rather than transformative level. The study also finds that TPACK integration contributes positively to student engagement, digital literacy, and higher-order thinking skills, yet its implementation is often instrumental and highly dependent on teachers’ reflective and integrative competencies. Furthermore, this study proposes a typology of pedagogical transformation and TPACK integration models, while critically highlighting the limitations of TPACK in addressing the value-based nature of Islamic education. As a result, the concept of Islamic-TPACK (i-TPACK) is introduced as a contextual framework that incorporates Islamic values into digital pedagogy. This study contributes theoretically by offering a comprehensive synthesis and conceptual refinement, although it is limited by its reliance on secondary data. Future research is recommended to empirically test the i-TPACK model and explore value-integrated digital learning practices in Islamic education contexts.